Implementasi Metode Outdoor Learning Melalui Pemanfaatan Lingkungan Sebagai Sumber Belajar Ipas Kelas IV Sd Candra Kasih, Kecamatan Denpasar Utara Kota Denpasar - Luh Gede Nandita Sukma Qianti; I Ketut Tanu; Gusti Ayu Dewi Setiawati (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
This study aims to describe in depth (1) the implementation of the outdoor learning method through the use of the environment as a learning resource in Natural and Social Sciences (IPAS) learning in grade IV of Candra Kasih Elementary School, North Denpasar District, (2) the obstacles and efforts faced in implementing the method, and (3) its impact on the learning process and outcomes of students. The background of this study is the low involvement and motivation to learn due to the dominance of the lecture method which makes learning passive and less contextual. The study uses a descriptive qualitative approach with observation, interview, documentation, and literature study techniques. The research subjects consisted of homeroom teachers and students. Data analysis refers to the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions/verification based on the pattern of findings and source triangulation. The results of the study indicate that the implementation of outdoor learning through the use of the school environment provides a contextual and enjoyable learning experience, and increases the active involvement of students. The environment is used as a concrete learning resource that connects the IPAS concept with everyday life through exploration of the school area and the use of real objects. This approach improves conceptual understanding, critical thinking skills, collaboration, and reflection. Obstacles that arose included time constraints, teacher preparedness in designing outdoor activities, and weather conditions. Efforts included thorough planning, collaboration with colleagues, and adapting activities to field conditions. Overall, the outdoor learning method had a positive impact on students' learning motivation, observation skills, and understanding of science concepts.